Analyses of Clinical and Biological Data for French and Belgian Immunocompetent Patients Infected With Hepatitis E Virus Genotypes 4 and 3 - Micas, Florence; Suin, Vanessa; Péron, Jean-Marie; Scholtes, Caroline; Tuaillon, Edouard; Vanwolleghem, Thomas; Bocket, Laurence; Lhomme, Sébastien; Dimeglio, Chloé; Izopet, Jacques; Abravanel, Florence (Frontiers in Microbiology, 2021)
Hepatitis E virus (HEV) genotypes 3 and 4 are the major causes of acute hepatitis in industrialized countries. Genotype 3 is mainly found in Europe and America, while genotype 4 is predominant in Asia. Several Japanese studies have suggested that genotype 4 is more virulent than genotype 3. We investigated this aspect by analyzing the clinical and biological data for 27 French and Belgian immunocompetent patients infected with HEV genotype 4. Their infections were probably acquired locally, since none of these patients reported traveling outside France or Belgium during the 2–8 weeks before symptoms onset. Each patient was matched for age (±5 years) and gender with two patients infected with HEV genotype 3. Bivariate analysis indicated that the HEV genotype 4-infected patients had significantly higher alanine aminotransferase (ALT) (2067 IU/L) and aspartate aminotransferase (AST) (1581 IU/L) activities and total bilirubin concentrations (92.4 μmol/L) than did those infected with HEV genotype 3 (1566 IU/L, p = 0.016; 657 IU/L, p = 0.003 and 47 μmol/L, p = 0.046) at diagnosis. In contrast, more patients infected with HEV genotype 3 reported dark urine (71% vs. 39%, p = 0.02) and experienced asthenia (89% vs. 58%, p < 0.01) than did those infected with HEV genotype 4. Two HEV genotype 4-infected patients died of multi-organ failure, while none of the genotype 3-infected patients died (p = 0.035). Finally, stepwise regression analysis retained only a greater increase in ALT (odds-ratio: 1.0005, 95% confidence interval: 1.00012–1.00084) and less frequent fever (odds-ratio = 0.1244; 95% confidence interval: 0.01887–0.82020) for patients infected with HEV genotype 4. We conclude that HEV-4 infections are likely to be associated with higher ALT activity than HEV-3 infections. Additional immunological and virological studies are required to confirm these findings and better understand the influence, if any, of genotype on HEV pathophysiology.